Divergent Synthesis of Disulfanes and Benzenesulfonothioates Bearing 2‐Aminofurans From N‐Tosylhydrazone‐Bearing Thiocarbamates. Issue 27 (14th June 2017) - Mai, Shaoyu; Song, Qiuling
Abstract: An efficient and convenient synthesis of valuable disulfanes and benzenesulfonothioates, having a 2‐aminofuran framework, has been developed by employing a copper‐catalyzed transformation of readily available N‐tosylhydrazone‐bearing thiocarbamates. This method features an inexpensive metal catalyst, mild reaction conditions, good functional‐group tolerance, short reaction times, and delivers valuable and complex products. A copper carbene generated from an N‐tosylhydrazone‐bearing thiocarbamate is proposed as the key intermediate for the transformation and it triggers the subsequent cascade. Remarkably, the Ts anion released from N‐tosylhydrazone further serves as a nucleophile, thus rendering the formation of benzenesulfonothioates under controlled conditions. Abstract : Waste not : N‐tosylhydrazone‐bearing thiocarbamates prove to be valuable substrates for access to complex disulfanes and benzenesulfonothioates with a 2‐aminofuran framework, when a copper‐catalyzed transformation is employed. Remarkably, the 4‐toluenesulfonyl (Ts) moiety, which usually is considered a waste product released from N ‐tosylhydrazone, serves as a nucleophile, thus leading to the formation of benzenesulfonothioates under controlled conditions.